A Study on the development of competitiveness index for digital logistics city - KIM, Youngseon (KDI School, 2024)
Today, countries around the world are seeking various strategies to solve the problems of the existing logistics industry due to rapid social and economic changes caused by the Fourth Industrial Revolution and to strengthen national competitiveness through technological innovation in the logistics industry. In July 2021, Korea established the 5th National Logistics Basic Plan to prepare a promotion strategy to become a global logistics leader. It aims to increase sales of the logistics industry to 140 trillion won by 2030 and to raise LPI to the top 10 globally by 2030, creating a sustainable logistics industry environment, strengthening industrial competitiveness, and improving market constitution. In addition, the government selected a digital logistics pilot city to solve the urban logistics problem and apply digital logistics technology in the design and planning stage of the city. Accordingly, this study aims to develop a competitiveness index model that can grasp the absolute level of competitiveness in digital logistics cities for the successful promotion of digital logistics cities.
Thesis(Master) -- KDI School: Master of Public Management, 2024
Keywords: Business logistics--Technological innovations